Corporate Resilience and Competitiveness Relying on System Digitalization Through Ambidextrous Innovation - Eduard Alfian Syamsya Sijabat; Hosianna Ayu Hidayati (Jurnal Teknologi dan Manajemen, 2024)
The business process of shipping agencies in the post-pandemic is facing adjustments in providing services to customers. A digitalization system carried out by shipping agencies is a solution to respond to these changes and enable shipping agency businesses to survive. This study explored the extent of the impact of system digitalization on the resilience of shipping agency companies and also on the company's competitive advantage mediated by ambidextrous innovation. This study was conducted on 192 shipping agency companies that are members of shipping agency associations in Indonesia's main ports. Data collection was carried out by distributing questionnaires online then data processing was carried out and analysis was carried out, both descriptive statistical analysis and inferential statistics using WarPLS. The research results showed that the existence of a system digitalization program increases company resilience. Likewise, the existence of a system digitalization program also increases the company's competitive advantage. With a proactive response in the form of ambidextrous innovation from the company, digitalization is increasingly showing a significant influence on the company's resilience and also on the company's competitive advantage. The results of this research provide additional empirical contributions in proving the RBV-based theory of competitive advantage where with breakthrough innovation and adaptation to digitalization of the system which is part of the empowerment of company resources aimed at producing service products that are of unique value and cannot be imitated by competitors so that they have a competitive advantage for the company. The results of this research also provide a practical contribution to the shipping agency industry where it cannot be denied that the system digitalization process followed by ambidextrous innovation will increase the company's resilience and produce competitive advantage for the company as well.